Creating heritage in the mining-impacted Barroso region (Portugal): a tool for subaltern environmental resistance? - Monaci; Sa Rego, J.; Amoedo, Diego (SIEF2025: Unwriting, 2025)
Creating heritage in the mining-impacted Barroso region (Portugal): a tool for subaltern environmental resistance? This communication aims to demonstrate how heritagization practices, guided by the principles of the UNESCO 2003 Convention for the Safeguarding of the Intangible Cultural Heritage, can empower communities to craft ecological integrated narratives that challenge the dominant extractivist discourses tied to the energy transition. The Barroso region is recognised as a Global Important Agricultural Heritage Systems by the FAO. At the same time, Covas do Barroso, a pillar parish of the Barroso landscape, have been under scrutiny for lithium extraction for over two decades. Its common land (baldios in Portuguese) is officially threatened with land grabbing. This rationale relies on a process of devaluation - a cheapening of people, their territory and their system of knowledge - that follows patterns of colonial dispossession threatening livelihoods globally. As a resistance strategy, the local authorities and the commoners decided to inventory the practices and knowledge of their baldios for an inscription in the Intangible Cultural Heritage National Inventory. Working with the socio-environmental research startup, the RHE Initiative, this effort revealed that such living heritage made of agropastoral practices and commons’ management, is vital for landscape conservation and climate resilience. Not only, those same practices are bearers of environmental values deeply embedded in traditional landscape management, they also provide livelihood for the local community. Through the intangible cultural heritage concept, communities were empowered to speak off their own subaltern environmental counter-narrative, based on a dwelling perception of the environment, challenging extractivist paradigms of development.